Five years of the #RSCPoster Twitter conference. Issue 89 (22nd October 2020) - Baker, Matthew J.; Gempf, Kathryn L.; McDonald, Hannah; Kerr, Hannah E.; Hodges, Catherine; Anastasaki, Athina; Noel, Timothy; Randviir, Edward P.
Abstract : #RSCPoster is a 24 hour poster conference on Twitter. The format has enabled hundreds to share research, with 32 million measurable impressions of #RSCPoster in 2020, participation growth each year and inspiring of new conferences. We outline of the history and content of the event. Abstract : The #RSCPoster Twitter conference is an annual, 24 hour poster conference held each March on Twitter. This original conference format has enabled hundreds of participants to share their research, with 32 million measurable impressions of #RSCPoster in 2020, participation growing each year and inspiring new conferences. Here, we will give a brief outline of the history, technicalities and content of the event.